2008
DOI: 10.1016/j.cellsig.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

hSef potentiates EGF-mediated MAPK signaling through affecting EGFR trafficking and degradation

Abstract: Sef (similar expression to fgf genes) was identified as an effective antagonist of fibroblast growth factor (FGF) in vertebrates. Previous reports have demonstrated that Sef interacts with FGF receptors (FGFRs) and inhibits FGF signaling, however, its role in regulating epidermal growth factor receptor (EGFR) signaling remains unclear. In this report, we found that hSef localizes to the plasma membrane (PM) and is subjected to rapid internalization and well localizes in early/ recycling endosomes while poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…IL-17RD has recently been shown to inhibit FGF signaling [28][29][30][31][32][33] and to facilitate EGF signaling [43]. In this report, we provide data showing that IL-17RD functions in IL-17 signaling, suggesting that IL-17RD has two distinct types of functions.…”
Section: Discussionsupporting
confidence: 52%
“…IL-17RD has recently been shown to inhibit FGF signaling [28][29][30][31][32][33] and to facilitate EGF signaling [43]. In this report, we provide data showing that IL-17RD functions in IL-17 signaling, suggesting that IL-17RD has two distinct types of functions.…”
Section: Discussionsupporting
confidence: 52%
“…In previous studies, IL17RD prevented degradation of EGFR and potentiated EGF signaling in HEK293T human embryonic kidney cells (27). As such, we explored the effect of IL17RD over-expression on proliferation of colon cancer cells with or without EGF treatment.…”
Section: Resultsmentioning
confidence: 81%
“…Interestingly, IL17RD has been described to inhibit tumorigenesis in vitro through antagonistic effects on fibroblast growth factor (FGF) signaling and inhibition of MAP kinase (MAPK) signaling (22,26,44). In contrast to this tumor suppressing mechanism, Ren et al demonstrated a dual role of IL17RD whereby IL17RD potentiates epidermal growth factor (EGF)-mediated MAPK signaling in the presence of EGF, whereas it exerts opposing effects in the presence of FGF (27). Our findings support this mechanism as basal cell proliferation was inhibited by IL17RD in the absence of EGF treatment, but IL17RD transfection increased cell proliferation in the presence of EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Tnfaip3 is an inhibitor of NF-.B activation, and studies suggest that it is a negative regulator of inflammation (30). In a study of influenza, infection in murine lungs induced Tnfaip3, and overexpression attenuated NF-.B promoter activity in bronchial epithelial cells after infection (31). In a model of airway inflammation, the overexpression of Tnfaip3 decreased inflammation (30).…”
Section: Discussionmentioning
confidence: 98%